The impact of anthropomorphism, consumer trust, and consumer attitude on purchase decisions of environmentally friendly products - Munawar, Fansuri; Handayani, Rini; Nilasari, Irma; Yudanegara, Aditya; Oktaviani, Desy (Institute of Computer Science (IOCS), 2023)
Environmentally friendly product purchase behavior is receiving increasing attention in the current marketing literature because understanding it is critical to the growing number of companies developing and marketing green products. However, only some know the importance of environmentally friendly products that can reduce adverse environmental effects. This study aims to analyze the factors that can increase consumer purchasing decisions for this environmentally friendly product. This study examines anthropomorphism, consumer trust, and attitudes toward purchasing decisions for environmentally friendly products. Sampling was conducted on 200 respondents who use environmentally friendly products in Bandung. The data analysis used is a structural equation model based on partial least squares (SEM-PLS) with the help of SmartPLS 3.0. All hypotheses in this study were accepted based on the data processing results. It means that anthropomorphism can have a positive effect on consumer trust and consumer attitudes. In addition, anthropomorphism, consumer trusts, and consumer attitudes can also directly influence the purchasing decisions of environmentally friendly products.